2019
DOI: 10.1177/1541204019854799
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences (ACEs) and Gang Involvement Among Juvenile Offenders: Assessing the Mediation Effects of Substance Use and Temperament Deficits

Abstract: A growing body of research has demonstrated the deleterious effects of adverse childhood experiences (ACEs). Less understood is the role of ACEs in gang involvement among juvenile offenders. The current longitudinal study employs a sample of 104,267 juvenile offenders (mean age of 16, 76% male, 46% Black non-Hispanic, 15.7% Hispanic) to examine the effect of ACE exposure on two different measures of gang involvement by age 18. We use structural equation modeling to test whether higher ACE exposure at Time 1 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 131 publications
(161 reference statements)
4
44
0
Order By: Relevance
“…Consistent with other recent studies [ 17 , 18 , 25 , 26 , 27 ], the current models show convincingly that the etiology of low self-control also has a more pathological basis in terms of trauma exposure, a concept largely overlooked in [ 20 ]. Moreover, trauma has a double-pronged effect on self-control as the abusive, neglectful, or traumatic event and the emotional and psychological reaction to it reduce self-control in youth.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with other recent studies [ 17 , 18 , 25 , 26 , 27 ], the current models show convincingly that the etiology of low self-control also has a more pathological basis in terms of trauma exposure, a concept largely overlooked in [ 20 ]. Moreover, trauma has a double-pronged effect on self-control as the abusive, neglectful, or traumatic event and the emotional and psychological reaction to it reduce self-control in youth.…”
Section: Discussionsupporting
confidence: 91%
“…On this empirical foundation, recent research has attempted to specify the personality and dispositional characteristics that result from traumatic exposure as well as potentially mediate the association between adverse events and delinquency [ 15 , 16 , 17 , 18 , 19 ]. Prominent in criminology [ 20 ], low self-control is a disposition characterized by poor emotional regulation or temper, impulsivity, self-centeredness, action as opposed to cognitive orientation, and poor gratification delay and has broad associations with antisocial behavior [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whether such early behavioral issues rise to the level of a behavioral disorder, such a path toward gang involvement and delinquency may still emerge. There are a multitude of shared risk factors predictive of both gang membership and delinquency, such as adverse childhood experiences, academic failure and school problems, substance abuse, and deviant peer associations (Thornberry et al, 2003; Wolff et al, 2020). In addition, the gang-delinquency relationship is complex and rather transactional/reciprocal where one must not necessarily precede the other, but rather each increases the odds of the other.…”
Section: Discussionmentioning
confidence: 99%
“…A second explanatory mechanism linking substance use and offending is through gang involvement. Using a sample of over 100, 000 juvenile offenders, Wolff et al (2020) found a relationship between ACE scores and both self-report and official measures of gang involvement by age 18. Furthermore, this relationship was mediated by the effect of ACEs on substance use and a difficult temperament.…”
Section: Juvenile Offending Outcomesmentioning
confidence: 96%